2018
DOI: 10.1155/2018/4285268
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Tear Inflammatory Cytokines as Additional Finding in Keratoconus Patients and Their First Degree Family Members

Abstract: Keratoconus is a progressive corneal ectasia that may lead to severe visual impairment due to the irregular astigmatism caused by corneal thinning. In addition to its association with atopy, eye rubbing, or genetic component, late reports suggest the involvement of inflammation in the pathogenesis of the disease. Our aim was to determine the concentration of IL-4, IL-6, IL-10, RANTES, IFN gamma, and TNF alpha in the tear film of patients with keratoconus and their first degree family members. We analyzed forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…Finally, we demonstrate that the effects of ISR modulation are specific to diseased cells, with ISRIB stimulating increased COL1A1 transcription and hydroxyproline production in KC cells only. We also investigated the expression of prospective inflammatory cytokines IL-1β and TNFα, which have been described as being dysregulated in keratoconus 36. We observed that both IL-1β and TNFα were not produced above the detection threshold by DN or KC fibroblasts under untreated conditions and, although there was a trend toward increased expression (by qPCR and ELISA), in both cases the levels of expression were barely above the detection threshold.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, we demonstrate that the effects of ISR modulation are specific to diseased cells, with ISRIB stimulating increased COL1A1 transcription and hydroxyproline production in KC cells only. We also investigated the expression of prospective inflammatory cytokines IL-1β and TNFα, which have been described as being dysregulated in keratoconus 36. We observed that both IL-1β and TNFα were not produced above the detection threshold by DN or KC fibroblasts under untreated conditions and, although there was a trend toward increased expression (by qPCR and ELISA), in both cases the levels of expression were barely above the detection threshold.…”
Section: Discussionmentioning
confidence: 89%
“…Higher levels of proinflammatory or inflammatory cytokines were shown. 25,26 Dias et al 12 reported that T4 receptors have been found in the lacrimal gland, confirming that the tear producing gland is a target organ of T4 and the T4 level was elevated in the tears of patients with keratoconus. Likewise, Thanos et al's 17 study, in which tear samples were collected from all patients with keratoconus and thyroid gland dysfunction, from a group of patients with keratoconus but without thyroid gland dysfunction, and from a control group with both keratoconus and thyroid gland dysfunction, compared tear T4 in thyroid gland dysfunction and immunohistochemical staining of its receptors between patients with keratoconus and controls.…”
Section: Discussionmentioning
confidence: 90%
“…15,16 The inflammatory cytokines in the lacrimal tear in patients with keratoconus may alter the postoperative outcomes. 17 A special attention must be given to patients with dry eye disease or meibomian gland dysfunction who can be very unsatisfied after the surgery due to subjective symptoms, regardless of multifocal IOL implantation. In all cases, our clinical judgment was to decide the risk/benefit ratio before implanting a lens of this type.…”
Section: Methodsmentioning
confidence: 99%